AB1151 Month of birth affects the risk of rheumatic diseases: a nationwide case-control study. (15th June 2017) - Koo, N; Lee, J; Lee, BW; Kwok, S-K; Park, SH; Ju, JH
Abstract : Background: There have been several studies which demonstrated the impact of birth on the risk of certain diseases such as asthma or cardiovascular diseases. However, rheumatic diseases have not yet been thoroughly investigated in terms of association with birth month. Objectives: In this study, we sought to determine whether birth month or season could affect the risk of rheumatologic diseases. Methods: The birth month patterns of patients with rheumatic diseases were compared with to those of general population. We utilized the claims data of Health Insurance Review and Assessment Service (HIRA) which covers nearly 90% of total population in Korea. The associations between birth month/season and 32 diseases were investigated using logistic regression. Results: Our dataset included 17, 247, 458 (male 8, 224, 670; female 9, 022, 788) individuals from HIRA database from January, 1997 to August, 2015. Among 27 rheumatic diseases, 8 diseases including Crohn's disease (CD), ulcerative colitis (UC), rheumatoid arthritis (RA), systemic lupus erythematosus, polymyalgia rheumatica (PMR), ankylosing spondylitis (AS), multiple sclerosis, gout, fibromyalgia (FMS) were significantly associated with birth month (P<0.05). In terms of seasonality, CD, UC, RA, Sjogren's syndrome, PMR, AS, Gout, and FMS demonstrated significant difference. CD, UC and AS showed higher prevalence in individuals born in winter and lower prevalence in summer. On the other hand, people who were born in summer showed higher possibility to have gout and FMS compared to those born in winter. In consistent with previous reports, type 1 diabetes is more prevalent in those born in winter. Angina and myocardial infarction showed higher prevalence in patients born in spring and lower in fall. This consistency reflects the relevance of our dataset and methodology. Conclusions: We found significant impacts of birth month/season on various rheumatic diseases. Seasonal variation of infective agents, sun exposure or food ingestion during gestation or early infancy may explain the association between birth month/season and certain disease development. Disclosure of Interest: None declared